Materials and Structures Inspired by Human Heel Pads for Advanced Biomechanical Function - Zhiqiang Zhuang; Congtian Gu; Shunlin Li; Hu Shen; Ning Liu; Ziwei Li; Dakai Wang; Cong Wang; Linpeng Liu; Kaixian Ba; Bin Yu; Guoliang Ma (Biomimetics)
The heel pad, located under the calcaneus of the human foot, is a hidden treasure that has been subjected to harsh mechanical conditions such as impact, vibration, and cyclic loading. This has resulted in a unique compartment structure and material composition, endowed with advanced biomechanical functions including cushioning, vibration reduction, fatigue resistance, and touchdown stability, making it an ideal natural bionic prototype in the field of bionic materials. It has been shown that the highly specialized structure and material composition of the heel pad endows it with biomechanical properties such as hyperelasticity, viscoelasticity, and mechanical anisotropy. These complex biomechanical properties underpin its advanced functions. Although it is known that these properties interact with each other, the detailed influence mechanism remains unclear, which restricts its application as a bionic prototype in the field of bionic materials. Therefore, this study provides a comprehensive review of the structure, materials, biomechanical properties, and functions of the heel pad. It focuses on elucidating the relationships between the structure, materials, biomechanical properties, and functions of heel pads and proposes insights for the study of bionic materials using the heel pad as a bionic prototype. Finally, a research idea to analyze the advanced mechanical properties of heel pads by integrating sophisticated technologies is proposed, aiming to provide directions for further in-depth research on heel pads and inspiration for the innovative design of advanced bionic materials.